Isolated polycystic morphology: Does it affect the IVF treatment outcomes?. (April 2015) - Bezirganoglu, N.; Seckin, K. D.; Baser, E.; Karsli, M. F.; Yeral, M. I.; Cicek, M. N.
Abstract The aim of the current study was to compare women who have normal ovarian ultrasonographic findings and women with ovulatory polycystic ovary (PCO), in terms of IVF treatment outcome. The study was conducted at a tertiary referral hospital and included 906 women who underwent IVF treatment. Of these, 224 of the women had PCO (24.7%) and 682 of the women had normal ovarian morphology (75.3%) at the time of ultrasonographic examination prior to IVF. The treatment outcomes were compared between the two groups. In the PCO group, the number of oocytes at the size of > 16 mm, the overall number of collected oocytes and the number of fertilised oocytes were found to be significantly higher. Furthermore, the rates of implantation, biochemical pregnancy and clinical pregnancy were significantly higher in the PCO group (p < 0.05). The detection of PCO morphology on baseline ultrasonography in IVF candidates may be associated with higher treatment success.